Wrist injuries in snowboarding-simulation of a worst case scenario of snowboard falls - Lehner, S.; Geyer, T.; Michel, F. I.; Schmitt, K. U.; Senner, V. (Procedia Engineering, 2014)
Snowboarding is one of the most popular winter sports, particularly among adolescents and younger adults. The risk of injuries while snowboarding is higher compared with alpine skiing, with the wrist as the dominant injury region. In contrast to increasing numbers regarding helmet usage, acceptance for wearing wrist protectors is decreasing. To date the market offers a variety of wrist protection products for snowboarding which feature different protective elements. However, there are no minimum performance standards for snowboarding wrist protectors worldwide. Currently a harmonized international standard is under preparation to provide guidelines for minimum safety performance for all wrist protectors used in snowboarding.